EFFECT OF PACKAGING METHODS VARIATIONS OF CIANJUR BLACK RICE (ORYZA SATIVA L. INDICA) ON CHANGES IN BIOACTIVE COMPOUNDS AND SENSORY PROPERTIES DURING STORAGE AND COOKING. - Fitriani, Aisyah
Black rice is a functional food that has high bioactive compounds, contains antioxidants, high nutritional content, and other health benefits, and the physical properties of black rice are also considered to be better. However, the postharvest and processing of black rice can cause a decrease in bioactive compounds and antioxidants, including packaging and cooking methods into rice. The packaging material that can be used is polypropylene (PP) plastic as primary packaging because it is easy to find in the market. Then, kraft paper as a secondary packaging in black rice packaging to prevent light from entering the plastic packaging. This study determines the effect of packaging methods and cooking methods on the pattern of changes in the content of bioactive and sensory compounds and determines the appropriate packaging and cooking method of black rice to maintain the content of bioactive compounds and sensory properties of black rice and black rice. The design model used in this study was a simple completely randomized design (CRD), with packaging methods (standard, vacuum, and active packaging) and cooking methods (rice cooker and steamed). The analysis was carried out on black rice and the change of black rice into rice. The test variables consisted of antioxidant activity, total anthocyanin levels, total flavonoids, water content, color (rice and rice), and organoleptic tests The results showed that PP plastic packaging and kraft paper had no significant effect on the variables of total anthocyanin content, total flavonoid content, moisture content, color L value, and color a value in black rice. However, it had a significant effect on the % inhibition variable and the b value of black rice. The black rice packaging method used tends to increase the pattern of changes in antioxidant activity, total anthocyanin content, color, and sensory assessment with hedonic quality and tends to decrease the pattern of changes in total flavonoids and water content. The vacuum packaging treatment was considered better because it had the highest value on the content of antioxidant activity, total anthocyanins, as well as the assessment of the panelists who preferred black rice from all parameters (appearance, color, texture, and smell). In the vacuum method% inhibition of black rice was 31.41-77.70%, total anthocyanin content 12.26-35.78 mg/100g, total flavonoid content 16.89- 24.69?g/g, moisture content 9.83- 18.446%, and the L value 23.86-25.67. The process of cooking rice into rice using a rice cooker had the smallest change in inhibition percentage, total anthocyanin content, and total flavonoid content, as well as the largest changes in water content and color. Black rice and black rice can still be accepted by panelists until the 60th day of storage.